Papiloma Sinonasal dan Keganasan Terkait Papiloma Sinonasal: Studi dari Pusat Rujukan Tersier di Indonesia - Sitinjak, David; Rachmadi, Lisnawati; Billianti, Yayi Dwina (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2022)
Background Sinonasal papilloma is a benign tumor arising from Schneiderian epithelia in sinonasal mucosa. It has the propensity towards malignant transformation. This preliminary study aims to report clinicopathological aspects of sinonasal papilloma and its malignant transformation rate. Methods A descriptive, cross-sectional study was conducted in Anatomical Pathology Department, FKUI/RSCM over a period of 2014-2019) A total of 127 histologic specimens with diagnosis of sinonasal papilloma obtained from 80 cases. Results The prevalence of sinonasal papilloma among all sinonasal neoplasms is 17.6%. Inverted papilloma was the most common histologic type 91.3%, exophytic papilloma 6.3% and oncocytic papilloma 2.5%, among male (70%), age rate 50 years old. Malignant transformation of squamous cell carcinoma 12.5%, and recurrence 21.3%, nasal congestion was the most complaint 50%. Cases were usually in T3 of Krouse stage 37.5% and managed with functional sinus endoscopic surgery 51.3%. Histological parameters were grade II 54.4%, surface keratinization 17.5%, bony trabeculae 41.3%, nasal polyps 20% and dense lymphocytic infiltrates 53.8%, foam cell infiltrates 2.5%. Mild to moderate dysplasia 8.8% and severe dysplasia 18.8%. Conclusion Sinonasal papilloma was rare sinonasal benign tumor. Inverted papilloma type was local aggressive, recurrence, dysplastic and malignant transformation, among male, age 50 years old, main complaint of nasal congestion, in Krouse stage T3, and managed by Functional Sinus Endoscopy Surgery (FSES